The CLEC3B inhibits cellular proliferation and metastasis of cholangiocarcinoma through Wnt/β-catenin pathway - Wu, Shengze; Wang, Guangfeng; Xie, Yuwei; Wu, Tingting; Du, Fangqian; Jin, Chen; Dong, Bingzi; Zhu, Chengzhan (PeerJ, 2024)
Purpose Cholangiocarcinoma (CCA) is a cancer of the biliary system, including intrahepatic and extrahepatic cholangiocarcinoma, and is highly aggressive. C-type lectins family member 3b (CLEC3B) is a Ca2+ binding transmembrane protein with different biological functions in a variety of cancers. The objective of this study was to explore the biological function of CLEC3B in CCA. Methods The CLEC3B gene was identified using the TCGA database and survival analysis of the cholangiocarcinoma clinical cohort. The expression CLEC3B cholangiocarcinoma and correlation with prognosis was investigated in our patient cohort. The effects of CLEC3B on proliferation, apoptosis, migration and invasion were verified in QBC939 and HUCCT1 cells. The effect of CLEC3B on the tumor formation was proved by xenograft tumor model in nude mice. The signaling pathway of CLEC3B in regulating CCA progression was further analyzed RNA sequencing and western blot. Results CLEC3B was decreased in the cholangiocarcinoma in the database. The mRNA and protein expression level of CLEC3B were significantly lower and correlated with poor overall survival in cholangiocarcinoma of our patient cohort. In vitro experiments proved that overexpression of CLEC3B can inhibit proliferation, migration and invasion in bile duct cancer cells. The CLEC3B was correlated with epithelial–mesenchymal transition and apoptosis. The calcium could promote the biological function of CLEC3B. The vivo study indicated that CLEC3B inhibited tumor formation. RNA sequencing indicating CLEC3B may transduce signal through e Wnt/β-catenin signaling pathway. Conclusions The CLEC3B inhibits cellular proliferation and migration of cholangiocarcinoma through the Wnt/β-catenin pathway.
Keywords: CLEC3B; Cholangiocarcinoma (CCA); Proliferation; Migration; Calcium